UMOWA NAJMU OKAZJONALNEGO LOKALU - Mróz, Arkadiusz (Zeszyty Prawnicze, 2017)
The Occasional Tenancy Agreement Summary This article presents issues relating to the structure of occasional tenancy and its practical significance for the operations of the residential rental market. The article explains the essence of occasional tenancy and discusses the origin of this institution, includingissues relating to the subject, parties, form and content of the occasional tenancy agreement, and the term for which such an agreement may be concluded, the rent and conditions for its revision, the possibility of a mandatory deposit being put on an occasional tenancy agreement, as well as the content and nature of annexes to such an agreement.